2016
DOI: 10.1089/sur.2015.207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Triclosan-Coated Suture and Antibiotic Prophylaxis on Infection and Recurrence after Karydakis Flap Repair for Pilonidal Disease: A Randomized Parallel-Arm Double-Blinded Clinical Trial

Abstract: We believe that antibiotic prophylaxis is necessary in patients scheduled for Karydakis flap repair. In our study, TCS tended to be associated with a lower rate of infection, but this trend did not achieve statistical significance. Anaerobic micro-organisms dominated the infective isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Study characteristics are summarised in table 1. Twenty-five RCTs were included in this review involving 11 957 patients 2 7 11 33 34 38–57. There were 6008 patients randomised to triclosan-coated sutures and 5949 patients to standard sutures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study characteristics are summarised in table 1. Twenty-five RCTs were included in this review involving 11 957 patients 2 7 11 33 34 38–57. There were 6008 patients randomised to triclosan-coated sutures and 5949 patients to standard sutures.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies were multicentre, with the remainder single-centre studies (n=17). Vicryl was compared with Vicryl Plus in 12 studies,11 34 39–41 43 46–49 54 56 3 studies compared PDS versus PDS Plus,7 38 55 1 study compared PDS II with PDS II Plus,44 2 study compared Monocryl against Monocryl Plus,45 57 1 compared Chinese silk with Vicryl Plus,53 4 studies compared Vicryl and Monocryl versus Vicryl Plus and Monocryl Plus33 50–52 and 2 studies compared Vicryl and PDS versus Vicryl Plus and PDS Plus 2 42…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomised parallel-arm double-blinded trial comparing antimicrobial prophylaxis vs no prophylaxis in patients undergoing Karydakis flap reconstruction, the no prophylaxis arm was terminated prematurely because of a significantly higher rate of infectious complications. 38 In addition, this trial demonstrated no significant benefit from the use of triclosan-coated sutures. To date, there has been little level 1 evidence to recommend antimicrobial prophylaxis for pilonidal excision with primary closure, although this may not be applicable to flap reconstruction techniques.…”
Section: Antimicrobialsmentioning
confidence: 78%
“…Although antimicrobial prophylaxis was not associated with improved rates of SSI and wound healing in excision with primary closure in the aforementioned systematic review, this lack of benefit may not apply to flap reconstruction. In a randomised parallel‐arm double‐blinded trial comparing antimicrobial prophylaxis vs no prophylaxis in patients undergoing Karydakis flap reconstruction, the no prophylaxis arm was terminated prematurely because of a significantly higher rate of infectious complications . In addition, this trial demonstrated no significant benefit from the use of triclosan‐coated sutures.…”
Section: Adjuncts To Surgerymentioning
confidence: 99%